Faktor-Faktor Yang Mempengaruhi Produksi Padi Sawah Di Desa Daleng Kecamatan Lembor Kabupaten Manggarai Barat - Runu, Emilia Kristi Wela; Hendrik, Ernantje; Bano, Maria; Suek, Johanna (Undana Press, 2024)
This research was conducted in Daleng Village, Lembor District, West Manggarai District. The purpose of this study was to fine out the general overview of field rice farming and determine the influence of seeds, fertilizer, land area and labor on field rice production. This research method involved random sampling of 30 % of a total of 224 field rice farmers, so that 67 people were selected are samples. The data used in this research comes from primary and secondary data. Data collection was carried out through interviews and documentation. The collected data was than analyzed using the Cobb-Douglas production function and processed using the SPSS version 16 program. The research results show that the stages of field rice farming activities include land processing, seed preparation, seeding, planting, fertilizing, weeding, harvesting and post-harvest. Based on analysis using the Cobb-Douglas Production function, the following output is obtained : Y = 5,168 X10,284 X20,064 X30,144 X40,457. The simultaneous F test show that together the independent variables have a significant effect on field rice production. Partially test (t test), land area, fertilizer, and labor have a positive and significant effect on field rice production, while seeds have a positive and insignificant effect on field rice production. The adjusted R2 amounting to 0,592 indicates that the combination of production factors of land area, seeds, fertilizer, and labor can simultaneously explain the dependent variable, namely field rice production, amounting to 59,2%. The remaining 40,8% is influenced by other factors not included in the regression model.